2006
DOI: 10.1021/jm050570f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of 3-[(2-Methyl-1,3-thiazol-4-yl)ethynyl]pyridine Analogues as Potent, Noncompetitive Metabotropic Glutamate Receptor Subtype 5 Antagonists; Search for Cocaine Medications

Abstract: Recent genetic and pharmacological studies have suggested that the metabotropic glutamate receptor subtype 5 (mGluR5) may represent a druggable target in identifying new therapeutics for the treatment of various central nervous system disorders including drug abuse. In particular, considerable attention in the mGluR5 field has been devoted to identifying ligands that bind to the allosteric modulatory site, distinct from the site for the primary agonist glutamate. Both 2-methyl-6-(phenylethynyl)pyridine (MPEP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 47 publications
(103 reference statements)
4
62
1
1
Order By: Relevance
“…These data suggest that acamprosate can antagonize metabotropic glutamate receptors as well as ionotropic glutamate receptors. Indeed, the mGlu5 antagonist 2-methyl-6-(phenylethynyl)-pyridine attenuates both cocaine-and cue-induced reinstatement of cocaine-seeking behavior (Backstrom and Hyytia 2006;Iso et al 2006;Lee et al 2005). However, mGlu5 antagonists also attenuate baseline cocaine self-administration patterns (Chiamulera et al 2001;Kenny et al 2003Kenny et al , 2005Tessari et al 2004), an effect that was not observed with acamprosate in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…These data suggest that acamprosate can antagonize metabotropic glutamate receptors as well as ionotropic glutamate receptors. Indeed, the mGlu5 antagonist 2-methyl-6-(phenylethynyl)-pyridine attenuates both cocaine-and cue-induced reinstatement of cocaine-seeking behavior (Backstrom and Hyytia 2006;Iso et al 2006;Lee et al 2005). However, mGlu5 antagonists also attenuate baseline cocaine self-administration patterns (Chiamulera et al 2001;Kenny et al 2003Kenny et al , 2005Tessari et al 2004), an effect that was not observed with acamprosate in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…Likewise, many members of the CDPPB series can also act as allosteric potentiators of mGluR1, but none of these compounds has neutral or allosteric antagonist activity at mGluR1 . Furthermore, analysis of analogs of MPEP has yielded many allosteric antagonists and a small number of neutral ligands but no allosteric potentiators in the MPEP series (Gasparini et al, 1999;Alagille et al, 2005a,b;Rodriguez et al, 2005;Iso et al, 2006). This suggests clear differences in the structural requirements of different activities at allosteric sites on mGluRs.…”
Section: Discussionmentioning
confidence: 99%
“…Most profoundly, mGluR5-null mutant mice are insensitive to the locomotor-stimulating and rewarding properties of cocaine [19]. Consistent with this phenotype, the mGluR5 specific antagonists, MPEP and MTEP, attenuate cocaine-mediated behaviors [61], including cue-induced relapse to cocaine seeking [5,19,48]. These antagonists also disrupt reinforcing properties of alcohol [76].…”
Section: Group I Mglurs and Addictionmentioning
confidence: 99%